PERKEMBANGAN KINERJA KEUANGAN PENGARUHNYA TERHADAP HARGA SAHAM DAN KEUNTUNGAN SAHAM - Inung Wijayanti; Laela Lanjarsih (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2016)
This study aims to determine the influence of financial performance that is the development of sales, earnings per share, dividend payout ratio, the price earnings ratio, debt to equity ratio, total asset to the stock price and dividend level either partially or simultaneously. The population in this study is a manufacturing company engaged in the sector of consumer goods industry and listed on the Stock Exchange 2009-2014. In purposive sampling, the sample used is about 18 compa-nies. The analysis used is multiple linear regression analysis and hypothesis test with significance level was set at 5%. In testing that has been done, the result that in partial development of earnings per share, dividend payout ratio, the price earnings ratio, debt to equity ratio significantly influence stock prices and stock profit rate. While the Improvement of sales and total assets does not affect into stock prices and stock profit rate. Simultaneously the development of sales, earnings per share, dividend payout ratio, the price earnings ratio, debt to equity ratio, total asset effect on stock prices and stock profit rate.